1963
DOI: 10.1126/science.142.3599.1585
|View full text |Cite
|
Sign up to set email alerts
|

Tree Rat, Thamnomys surdaster surdaster , in Laboratory Research

Abstract: The breeding of successive generations of Thamnomys in the laboratory made possible a study of its bionomics and an evaluation of its importance in parasitological and malarial research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1964
1964
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In laboratory conditions the African tree rat does not seem to be able to attain its full reproductive capacity-this is not due to effects on litter size so much as an inability to regularly attain the minimum interval between litters. The normal litter size of two, three or four young found during this study agrees with those reported previously (Rodhain, 1954;Yoeli, Alger & Most, 1963). The present data indicate that pregnancy can recur at 28-29 day intervals but does not always do so.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In laboratory conditions the African tree rat does not seem to be able to attain its full reproductive capacity-this is not due to effects on litter size so much as an inability to regularly attain the minimum interval between litters. The normal litter size of two, three or four young found during this study agrees with those reported previously (Rodhain, 1954;Yoeli, Alger & Most, 1963). The present data indicate that pregnancy can recur at 28-29 day intervals but does not always do so.…”
Section: Discussionsupporting
confidence: 93%
“…Thus when fertilization occurs lactation is already well established. In all other aspects of female reproduction Grummomys is very similar to the laboratory rat with the exception of the number of teats and the well-documented tenacity with which the young of the former attach themselves to the teats during the first 16 days or so of lactation (Rodhain, 1954;Yoeli et al, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Ambient temperature should not exceed 25 °C. Details on breeding G. surdaster thicket rats can be found in Yoeli et al. (1963).…”
Section: Methodsmentioning
confidence: 99%
“…Already in 1962, a breeding colony with animals captured in what is now R.D. Congo, was established for studies on Plasmodium , Leishmania , Trypanosoma and other parasites (Yoeli et al. 1963).…”
Section: Introductionmentioning
confidence: 99%
“…It occupies a diverse range of habitats, from tall grasses to forests, and its diet consists primarily of fruits, plant material and insects (Kingdon 1984;Wirminghaus & Perrin 1992). The life history of G. dolichurus has been well studied in captivity since the species has served as an experimental animal in malaria studies, but very little is known about its ecology in the wild (Yoeli et al 1963;Bland 1973).…”
Section: Study Site and Study Speciesmentioning
confidence: 99%